“Projeto Pele Alerta” : projeto educativo em prevenção e detecção precoce do câncer de pele direcionado a profissionais do mercado de beleza e cuidados pessoais - Machado, Caroline Kroeff [UNIFESP] (2017)
Introduction: Skin cancer is the most frequent in many countries, including Brazil and its incidence is still growing. Early detection is the best way of reducing morbidity and mortality. Body parts like head, neck and back are of hard visualization by the person themselves. Beauty professionals spend a long time in contact with their clients` skin and annexes, having visual access to places the clients themselves have a hard time viewing. There is a potential field in which beauty professionals are informed and help early detection skin cancer suspicious lesions, sending forward to medical evaluation and possible early treatment. Objective: To develop an online educational project, directed to professionals in the beauty and personal care market, about prevention and early detection of skin cancer. Methods: Creation of the “Pele Alerta” Project (PPA), with educational videos, visual support material and website. Results: This master degree’s product is the PPA. It can be accessed through www.projetopelealerta.com. There are 4 topics at the moment, each one with a corresponding video (YouTube) and support material in PDF. The topics are: “Os raios ultravioleta e a pele”; “O câncer de pele: nosso temido inimigo”; “Proteção solar: aproveitando o Sol da maneira correta”; “Onde suspeitar de alguma lesão? “. Conclusion: an educational project regarding skin cancer has been created, and it is accessible online anywhere in Brazil.